Acceleration of Village Welfare through Bumdes: Disorientation of Implementation of Bumdes Regulations and Policies - Rianda Dirkareshza; Eka NAM Sihombing (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
Village-Owned Enterprises (BUMDes) do not have legal certainty regarding their form of legal entity and it will make it difficult to meet the hope of all villagers to run businesses together in accordance with their characteristics, potential, and their respective resources. This research aims to provide input and solutions to the government to be able to accelerate the welfare of villages through BUMDes. The method used in this research is literary or library research by using normative juridical approach. In the processing of data, this journal used qualitative and quantitative approach. This research showed the result that there is disorientation in the implementation of BUMDes regulations and policies, such as: first, the incompatibility of village regulations with other laws and regulations. Second, the low community initiative in driving the village economy. Third, the vagueness of BUMDes position as a social and commercial institution. Fourth, policies that have not directed the professionalism of BUMDes. The solution in accelerating village welfare through BUMDes is to provide the flexibility of BUMDes in the form of legal entity as a bridge to be able to enlarge capital in the investment sector.